LOW TEMPERATURE BEHAVIORS OF LA-CA-(MN, FE)-O CMR MATERIALS - Hu J.F.; Mei L.M.; Qin H.W.; Zhao W.J.; Wang Y.Z. (My University, 2000)
The magnetic and magnetoresistance behavior of La Ca (Mn,Fe) O materials was investigated at low temperature. The result shows that with the increasing replacement of Mn by Fe, the ferromagnetic interaction of samples decreases but the antiferromagnetic interaction increases. The new phenomenon of the “bending” in the magnetization process and the field dependence of magnetoresistance were found in the sample with Mn:Fe=9:1 and the physical mechanism was studied. Small replacement of Mn by Fe increases the low temperature CMR value in La Ca (Mn, Fe) O materials.